EKSPLOITASI LINGKUNGAN HIDUP DALAM PERSPEKTIF SOLLICITUDO REI SOCIALIS (sebuah Bentuk Keprihatinan Gereja) - Adinuhgra, Silvester (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
Undeniably, the current natural charm is much damaged by various formsof exploitation. This real situation awakens a new awareness to the worldcommunity, including the Church, to voice its care in protecting nature. TheChurch voiced its prophetic tone, one of which is revealed in the encyclicalof Pope John Paul II, Sollicitudo Rei Socialis (SRS). SRS reveals that theemergence of Exploitation is caused by humans who lose respect for nature.